Early determinants of smoking in adolescence: a prospective birth cohort study Determinantes precoces do fumo na adolescência: uma coorte de nascimentos prospectiva - Ana M. B. Menezes; Pedro C. Hallal; Bernardo L. Horta (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2007)
In a prospective birth cohort study in Brazil, the prevalence and early risk factors for smoking in adolescence were investigated. All 1982 hospital-born children in Pelotas, Rio Grande do Sul, Brazil, were enrolled in a birth cohort study (N = 5,914; boys: 3,037; girls: 2,877). All male participants were searched in 2000 when enrolling in the national army, and 78.8% were traced. In 2001, a systematic sample of 473 girls was interviewed, representing a follow-up rate of 69.1%. Among males, 48.6% (95%CI: 46.6-50.7) had ever tried smoking and 15.8% (95%CI: 14.3-17.3) were daily smokers. Among females, 53.1% (95%CI: 48.6-57.6) had ever tried smoking and 15.4% (95%CI: 12.1-18.7) were daily smokers. Boys born to single mothers and those with fathers with low schooling were more likely to smoke in adolescence. Girls from low-income families, with mothers who smoked during pregnancy, and fathers with alcohol-related problems were more likely to smoke. Although the smoking prevalence was similar in boys and girls, risk factors for smoking were different between the sexes. Social environment appears to be the strongest predictor of tobacco use in adolescence. A prevalência e os determinantes precoces do fumo na adolescência foram investigados em uma coorte pros-pectiva de nascimento no Brasil. Todos os nascidos vivos em hospitais de Pelotas, no Sul do Brasil, em 1982 foram incluídos em um estudo de coorte de nascimentos (N = 5.914; meninos: 3.037; meninas: 2.877). Todos os participantes do sexo masculino foram procurados em 2000 durante o alistamento militar, e 78,8% foram localizados. Em 2001, uma amostra sistemática de 473 meninas foi entrevistada, representando uma taxa de acompanhamento de 69,1%. Entre os homens, 48,6% (IC95%: 46,6-50,7) já haviam experimentado cigarro e 15,8% (IC95%: 14,3-17,3) eram fumantes diários. Entre as meninas, 53,1% (IC95%: 48,6-57,6) já haviam experimentado cigarro e 15,4% (IC95%: 12,1-18,7) eram fumantes diárias. Meninos filhos de mães solteiras e de pais com baixa escolaridade tiveram maior probabilidade de fumar na adolescência. Meninas pertencentes a famílias de baixa renda, com mães que fumaram durante a gravidez e pais com problemas relacionados ao álcool apresentaram maior probabilidade de fumar. Embora a prevalência de fumo tenha sido similar entre meninos e meninas, os fatores associados ao fumo variaram entre os sexos. O ambiente social parece ser o preditor mais forte do uso de tabaco na adolescência.